2-(1H-Benzotriazol-1-yl)-1-(2-chlorobenzoyl)ethyl 4-methylbenzoate - Jiang, Lin-Bin (International Union of Crystallography, 2008)
In the molecule of the title compound, C(23)H(18)ClN(3)O(3), the essentially planar benzotriazole ring makes dihedral angles of 52.93 (1) and 85.21 (1)°, respectively, with the chlorophenyl and tolyl rings. The crystal packing is stabilized by π–π [centroid-to-centroid distance 3.830 (2) Å, interplanar distance 3.705 Å, slippage 0.968 Å]; C—H⋯π⋯tolyl ring interactions are also present.